Acute posterior multifocal placoid pigment epitheliopathy (APMPPE) – a therapeutic dilemma - Kubicka-Trząska, Agnieszka; Oleksy, Piotr; Karska-Basta, Izabella; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To present a rare idiopathic inflammation of the posterior segment of the eye - acute posterior multifocal placoid pigment epitheliopathy (APMPPE). Material and methods: A 17 years old male patient was referred to the Department of Ophthalmology of Medical College, Jagiellonian University in Krakow with the diagnosis of bilateral choroiditis of unknown etiology. The patient underwent the basic ophthalmological examination followed by fluorescein (FA) and indocyanine green (ICGA) angiography. Laboratory testing for Lyme disease, sarcoidosis and syphilis, as well as genetic testing, to determine the presence of HLA antigen complex, were performed Results: Based on the outcomes of performed investigations the definitive diagnosis of APMPPE was established. Systemic steroidotherapy was initiated due to rapid progression of the inflammatory changes, progression of the central visual field changes and profound visual acuity deterioration. Conclusions: APMPPE is a rare, inflammatory and idiopathic eye disease with no clear indications for pharmacological therapy. However decision about necessity and sort of pharmacological therapy should be taken under consideration individually for each patient.